How to Dissect Honey Bees (Apis mellifera L.) to Detect Tracheal Mites (Acarapis woodi Rennie) - John Bonkowski; Ashley N. Mortensen; James D. Ellis (EDIS)
Tracheal mites are parasites of the western honey bee and negatively impact the health and productivity of an infested colony. This 6-page fact sheet details the method of dissecting honey bees in order to diagnose tracheal mites. Written by John Bonkowski, Ashley N. Mortensen, and James D Ellis, and published by the UF Department of Entomology and Nematology, January 2015.